KEYS OF MIND - Wina Asry (Journal Analytica Islamica, 2021)
The purpose with the title Keys Of Mind is to find out the key to thinking.The pattern of human views in addressing a problem. Either studied from his pointof view or termed a point of view. Assessed through criticism in reviewing theinformation received. Examined through experience during adventure exploringphenomena that exist in the world, both broadly and specifically. In the end resultin understanding. The tradition is also related as the key to thinking becausesomething that affects the human perspective due to the teachings obtained fromchildhood to adulthood which in the process of traveling there are family,environmental and community factors. Furthermore, scales and variables are alsopart of the benchmark for the human perspective to combine or connect onemeaning with another.